PTH-158 Alcohol In-Patient Detox: Withdrawing the Burden of in Patient Management. (4th June 2013) - Barry, N; Vinayaga-Pavan, M; Turner, R; Wong, V S
Abstract : Introduction: In 2009–10, there were 1, 057, 000 alcohol related admissions to a hospitals in England 1 . Currently patients treatmented for alcohol withdrawal require hospital admission for at least 4–7 days, to complete medical detoxification. Previous studies have shown that even those patients who have severe symptoms of withdrawal, after 2–3 days, can be safely treated in an ambulatory environment 2 . The Aim: of this study was to identify the current burden of acute alcohol admissions to the medical unit, demographics of patients and the cost effectiveness of integrating an ambulatory care system. Methods: Retrospective data from six months of accident and emergency (A&E) admissions were reviewed from January 2012- June 2012. Patients admitted with acute alcohol intoxication or withdrawal were identified and patients notes analysed. Costings for management were estimated using data sourced from Department of Health Reference Costs 2011–12. Results: Of the 203 patients presenting to A&E with acute alcohol intoxication or withdrawal, 51 patients were treated for acute alcohol withdrawal (22 female, 29 male). The average age of patients was 60 years. 43% of patients were managed by acute assessment teams, 31% by gastroenterology, and 25% by general medicine. 2 patients required management in ITU. Mean length of stay 10.4 days. Of the patients reviewed the mean drinking years 8.03 with an average of 165 units of alcohol drunk per week. 50% of patients had with a documented mental health assessment, of which 74% had documented mental health conditions other than alcohol dependency. Mortality over this period was 0.1% and readmission within the six month period was averaged at 2.9 admissions. Cost of current 7 seven day inpatient admission with 4 hours of junior doctor input was costed at £2183.47 vs a three day admission with 3 three follow up ambulatory appointments and 2 two hours of junior doctor time costing £1352.57. Conclusion: The burden of alcohol related admissions requires an innovative approach to improve patient care and reduce readmissions. Our study has highlighted the possibility of utilising ambulatory care in selected patients as a method of improving care and reducing the cost of admissions to hospital. It also highlighted the importance of identifying patients as high risk of mental health issues. Previous work has identifed the benefits of outpatient withdrawal in abstenence and psychological well being3. Subsequent to this study our hospital has piloted an ambulatory care pathway and prospective analysis will be completed in due course. Disclosure of Interest: None Declared. References: www.ic.nhs.uk/pubs/alcohol12 Stockwell et al. Home detoxification from alcohol: its safety and efficacy in comparison with in-patient care. ALcohol and ALcoholism 26. 645–650 Fleeman et al. Alcohol home detoxification: A literature review. Alcohol and Alcoholism 32. 649–656